Pelayanan Akademik dan Kepuasan Mahasiswa (Studi Kasus Sekolah Tinggi Agama Islam Negeri Teungku Dirundeng Meulaboh) (BIDAYAH: STUDI ILMU-ILMU KEISLAMAN, 2018)
STAIN Teungku Direundeng Meulaboh is one of higher education institution in the Aceh that implements organizational activities with the delegation of management authority to fulfill the quality service to students in each program study. Academic service is an activity or a series of invisible activity that occurs through the interaction between students and staff provided by the campus administrators that aims to solve the student problems. The use of qualitative methods in this study was intended to obtain important aspects related to the implementation of academic and administrative services of STAIN Teungku Dirundeng Meulaboh. The survey on student satisfaction with the quality of the services provided by STAIN Teungku Dirundeng Meulaboh pointed that the level of faculties’ loyalty to the regulations set by STAIN Teungku Dirundeng Meulaboh was not optimal. There were lecturers who provided dissatisfactory services by not following the class up to seven times. Furthermore, almost all aspects of service quality that include empathy, reliability, and responsiveness were also not optimal.